Efficacy of Ceftazidime-avibactam Plus Aztreonam in Patients With Bloodstream Infections Caused by Metallo-β-lactamase–Producing Enterobacterales. (19th May 2020) - Falcone, Marco; Daikos, George L; Tiseo, Giusy; Bassoulis, Dimitrios; Giordano, Cesira; Galfo, Valentina; Leonildi, Alessandro; Tagliaferri, Enrico; Barnini, Simona; Sani, Spartaco; Farcomeni, Alessio; Ghiadoni, Lorenzo; et al.
Abstract: Background: In vitro data support the use of combination of aztreonam (ATM) with ceftazidime-avibactam (CAZ-AVI), but clinical studies are lacking. The aim of our study was to compare the outcome of patients with bloodstream infections (BSIs) due to metallo-β-lactamase (MBL)–producing Enterobacterales treated either with CAZ-AVI plus ATM or other active antibiotics (OAAs). Methods: This was a prospective observational study including patients admitted to 3 hospitals in Italy and Greece. The primary outcome measure was 30-day all-cause mortality. Secondary outcomes were clinical failure at day 14 and length of stay after BSI diagnosis. Cox regression analysis including a propensity score (PS) for receiving CAZ-AVI + ATM was performed to evaluate primary and secondary outcomes. A PS-based matched analysis was also performed. Results: We enrolled 102 patients with BSI; 82 had infections caused by NDM-producing (79 Klebsiella pneumoniae and 3 Escherichia coli ) and 20 by VIM-producing (14 K. pneumoniae, 5 Enterobacter species, 1 Morganella morganii ) strains. The 30-day mortality rate was 19.2% in the CAZ-AVI + ATM group vs 44% in the OAA group ( P = .007). The PS-adjusted analysis showed that the use of CAZ-AVI + ATM was associated with lower 30-day mortality (hazard ratio [HR], 0.37 [95% confidence interval CI, .13–.74]; P = .01), lower clinical failure at day 14 (HR, 0.30 [95% CI, .14–.65]; P = .002), and shorter length of stay (subdistributional HR, 0.49 [95% CI, .30–.82]; P = .007). The PS-matched analysis confirmed these findings. Conclusions: The CAZ-AVI + ATM combination offers a therapeutic advantage compared to OAAs for patients with BSI due to MBL-producing Enterobacterales. Further studies are warranted. Abstract : Limited treatment options are available for bacteremia due to MBL-producing Enterobacterales. The use of ceftazidime-avibactam plus aztreonam is associated with lower mortality compared to other active antibiotics. Combining ceftazidime-avibactam and aztreonam may be a reasonable treatment strategy for such infections.